ANALISIS PENGARUH SUDUT PULLEY DAN BERAT ROLLER TERHADAP DAYA DAN TORSI PADA MOTOR MATIC MODIFIKASI 110CC: ANALYSIS OF THE EFFECT OF PULLEY ANGLE AND ROLLER WEIGHT ON POWER AND TORQUE ON 110cc MODIFIED MATIC MOTORCYCLE - Bramastyo, Aditya (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2022)
Common complaints from users of standard and modified automatic scooters often revolve around the lack of power responsiveness when used in urban settings and overtaking vehicles on rural roads.The study aims to investigate the influence of variations in pulley angle and roller weight on the power and torque output of a modified 110cc automatic transmission scooter, The experimental research method was employed, analyzing the engine's performance data through power and torque measurements. The results revealed significant differences in power and torque among the tested pulley angle and roller weight variations. The combination of a 13.5° pulley angle and 10g roller weight exhibited the best performance, achieving 9.75 HP at 7000 RPM for power and 9.93 Nm at 7000 RPM for torque. It can be concluded that utilizing a 13.5° pulley angle and 10g roller weight contributes favorably to power and torque output in the modified 110cc automatic scooter.